Freshness Detection And Sorting Of Pears Using The TCS-3200 Sensor - Moch. Azriel Revanza; Syamsudduha Syahrorini; Akhmad Ahfas (Information Technology and Science (ITScience), 2023)
Pears in early autumn can be harvested with the best quality. Pear farmers sort the fruit so that it can be consumed and sold with the best quality. Therefore automatic detection and sorting tools can make it easier for farmers to sort pears. This tool can sort fresh and rotten fruit using the TCS-3200 sensor based on the ESP32 microcontroller. The harvested fruit is collected in a container and the fruit will go out onto the conveyor. The conveyor has a length of 60 cm using a Nema 17 stepper motor that moves automatically, the TCS-3200 sensor is placed in the middle of the conveyor so that it can detect moving pears. The results of the sorting door servo if the fruit is declared fresh then the servo remains closed straight so that the fruit will go to the front container, and vice versa the fruit is declared rotten then the servo will open up so that the fruit will go down. At the end of the conveyor there is an IR sensor which is used to send a signal to the servo motor of the main container door, so that if the fruit has been detected and leads to the IR sensor, the main container door will open and take out new pears. And for data collection the number of pears can be seen through the LCD by calculating the number of pears that have been detected, the number of fresh fruit and the number of rotten fruit, and the overall calculation of the amount of data can be seen through a spreadsheet. In this case, it is hoped that this research can help and facilitate farmers in harvesting fruit on a large scale while being efficient in time and energy.